Increasing Pizza Box Assembly Using Task Analysis and a Least-To-Most Prompting Hierarchy. - Stabnow, Erin F.; Rieger, Heather K.; Sweeney, William J. (Child & Family Behavior Therapy, 2023)
The purpose of this study was to determine whether a least-to-most prompting hierarchy was effective in teaching students with intellectual disabilities to increase the number of task-analyzed steps independently completed related to folding a pizza box as a potential pre-vocational task. An additional and related purpose of this study was to determine whether a least-to-most prompting hierarchy was effective for improving these students' productivity while decreasing the level of least-to-most prompts required to complete task-analyzed steps of a pizza box assembly task. A multiple-baseline design across subjects was used to analyze the effectiveness of the implementation of a least-to-most prompting hierarchy. Results of this study indicated that the use of a task analysis and a least-to-most prompting hierarchy was effective in teaching individuals with intellectual disabilities pizza box assembly skills. Implications and recommendations for the use of a task analysis with least-to-most prompts for teaching complex vocational tasks to individuals with intellectual disabilities as well as possibilities for future research were also discussed.